A prospective study of C-reactive protein in patients with obesity during IVF. (27th May 2021) - Haikin Herzberger, Einat; Miller, Netanella; Ghetler, Yehudith; Tamir Yaniv, Rina; Neumark, Eran; Shulman, Adrian; Wiser, Amir
Abstract: This prospective cohort pilot study investigated the physiology of C-reactive protein (CRP) during in vitro fertilization (IVF) cycles and its effect on outcomes in women with and without obesity. The study was conducted from April to August 2014, in the IVF Unit of a university-affiliated hospital. Women aged 18–42 years were enrolled. Those with chronic inflammatory diseases or acute illness were excluded. A total of 31 patients were included: 17 with BMI < 30 kg/m 2 and 14 with BMI ≥ 30 kg/m 2 . Serum CRP levels were measured: (i) before starting ovarian stimulation; (ii) on the day of β-HCG administration; and (iii) on day of ovum pick-up (OPU), in both serum and follicular fluid. Serum CRP levels were significantly higher in women with obesity at all time points. For the entire cohort, a positive correlation was found between basal oestradiol (E2 ) and basal CRP ( r = 0.71, p < 0.05). A specific pattern of CRP levels was not detected during the IVF cycle. High serum CRP levels on OPU day had a negative effect on embryo quality ( p = 0.056). CRP ≥ 0.5 mg/dL was associated with lower quality embryos (2.6 ± 0.3 vs. 3.3 ± 0.3; p = 0.04). High serum CRP level on OPU day negatively affects embryo quality.